2011
DOI: 10.1084/jem.20102657
|View full text |Cite
|
Sign up to set email alerts
|

Flt3L controls the development of radiosensitive dendritic cells in the meninges and choroid plexus of the steady-state mouse brain

Abstract: As shown by analyses of morphology, gene expression, antigen-presenting function, and Flt3 dependence, the steady-state mouse brain contains a population of DCs that exhibits similarities to splenic DCs and differences from microglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 57 publications
13
175
1
1
Order By: Relevance
“…Here, we found that the CP, under physiological conditions, retains a broad repertoire of CNS-specific CD4 + T-cell clones. These T cells, upon recognition and reactivation by their cognate antigens, potentially presented to them by the Flt3 + dendritic cells found in the CP (39), either enter the CSF or remain in the CP (40,41). Although TCR-seq of the CP allowed us to identify CNS-specific clonotypic enrichment both in young and aged mice, other parameters of age-related changes of the TCR repertoire should not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the CP, under physiological conditions, retains a broad repertoire of CNS-specific CD4 + T-cell clones. These T cells, upon recognition and reactivation by their cognate antigens, potentially presented to them by the Flt3 + dendritic cells found in the CP (39), either enter the CSF or remain in the CP (40,41). Although TCR-seq of the CP allowed us to identify CNS-specific clonotypic enrichment both in young and aged mice, other parameters of age-related changes of the TCR repertoire should not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The split between the two pathways was defined by Liu and Nussenzweig (64): Monocytes remain dependent upon M-CSF, and the dendritic cells remain dependent on flt-3L. The dendritic cell progenitor moves into lymphoid and nonlymphoid organs (64), the latest example being Kang Liu's research with the meninges of the brain (68). Niroshana Anandasabapathy is leading a new clinical study with Celldex Therapeutics to pursue flt-3L in people.…”
Section: Wwwannualreviewsorg • Decisions On Dendritic Cellsmentioning
confidence: 99%
“…Dendritic cells constitute approximately 1% of immune cells within the choroid plexus and meninges (87,88), but unlike the putative dendritic cells of the brain parenchyma, choroid plexus and meningeal dendritic cells are distinct from microglia and closely resemble classical dendritic cells that require FMSlike receptor tyrosine kinase 3 ligand for development (88). The CSF also contains a trafficking population of mononuclear cells, comprising T cells (90%), B cells (5%), monocytes (5%), and dendritic cells (Ͻ1%) (89).…”
Section: Immunosurveillance Of the Cnsmentioning
confidence: 99%